MyCare study: protocol for a controlled trial evaluating the effect of a community-based intervention on psychosocial, clinical outcomes and hospital admission rates for adults with severe mental illness. Issue 11 (23rd November 2020) - O'Donnell, Renée; Savaglio, Melissa; Fast, Debra; Vincent, Ash; Vicary, Dave; Skouteris, Helen
Abstract : Introduction: People with serious mental illness (SMI) often fail to receive adequate treatment. To provide a higher level of support, mental health systems have been reformed substantially to integrate mental healthcare into the community. MyCare is one such community-based mental health model of care. This paper describes the study protocol of a controlled trial examining the effect of MyCare on psychosocial and clinical outcomes and hospital admission and duration rates for adults with SMI. Methods and analysis: This is a multisite non-randomised controlled trial with a 3, 6 and 12-month follow-up period. The study participants will be adults (18–64 years of age) with SMI recruited from Hobart, Launceston and the North-West of Tasmania. The treatment group will include adults who receive both the MyCare intervention and standard mental health support; the control group will include adults who receive only standard mental health support. The primary outcome includes psychosocial and clinical functioning and the secondary outcome will examine hospital admission rates and duration of stay. Mixed-effects models will be used to examine outcome improvements between intake and follow-up. This trial will generate the evidence needed to evaluate the effect of a community mental health support programme delivered in Tasmania, Australia. If MyCare results in sustained positive outcomes for adults with SMI, it could potentially be scaled up more broadly across Australia, addressing the inequity and lack of comprehensive treatment that many individuals with SMI experience. Ethics and dissemination: This study has been approved by the Tasmanian Health and Medical Human Research Ethics Committee. The findings will be disseminated to participants and staff who delivered the intervention, submitted for publication in a peer-reviewed journal and shared at academic conferences. Trial registration number: ACTRN12620000673943.